2016
DOI: 10.3390/ph9030055
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 in Drug Development

Abstract: Transient receptor potential vanilloid 3 (TRPV3) is a member of the TRP (Transient Receptor Potential) super-family. It is a relatively underexplored member of the thermo-TRP sub-family (Figure 1), however, genetic mutations and use of gene knock-outs and selective pharmacological tools are helping to provide insights into its role and therapeutic potential. TRPV3 is highly expressed in skin, where it is implicated in skin physiology and pathophysiology, thermo-sensing and nociception. Gain of function TRPV3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 77 publications
(119 reference statements)
2
36
0
Order By: Relevance
“…Several companies have pursued selective antagonists of TRPV3 channels including Abbvie (Gomtsyan et al, ), Hydra Biosciences and Glenmark/Sanofi‐Aventis (Grubisha et al, ). The Glenmark/Sanofi‐Aventis compound GRC15300 failed a Phase 2 trial in chronic peripheral neuropathy patients (a 4 week trial), and the collaboration between the two companies was terminated in 2014 (Broad et al, ). However, recent reports suggest that these TRPV3 channel antagonists are not full blockers of the channel (Grubisha et al, ), so it is difficult to know how to interpret these results with regards to a potential role of TRPV3 channels in pain.…”
Section: Trpv3 Channels and Painmentioning
confidence: 99%
“…Several companies have pursued selective antagonists of TRPV3 channels including Abbvie (Gomtsyan et al, ), Hydra Biosciences and Glenmark/Sanofi‐Aventis (Grubisha et al, ). The Glenmark/Sanofi‐Aventis compound GRC15300 failed a Phase 2 trial in chronic peripheral neuropathy patients (a 4 week trial), and the collaboration between the two companies was terminated in 2014 (Broad et al, ). However, recent reports suggest that these TRPV3 channel antagonists are not full blockers of the channel (Grubisha et al, ), so it is difficult to know how to interpret these results with regards to a potential role of TRPV3 channels in pain.…”
Section: Trpv3 Channels and Painmentioning
confidence: 99%
“…For example, although published studies are limited, there are reports in the patent literature that TRPV3 antagonists can suppress certain forms of mechanical hypersensitivity in rats after nerve injury [111]. In addition, it was reported that, in the mouse acetone-ether-water model of chronic dry skin, the genetic absence of TRPV3 resulted in reduced scratching behavior [112].…”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…These particles (120,424) were then subjected to a no-alignment 3D classification using a soft mask of the full molecule. The best resolving class (27,620 particles) was then 3D auto-refined (C4 symmetry) to a final resolution of 3.4 Å, as estimated by gold-standard FSC 0.143 criterion 62,63 .…”
Section: Apo Trpv3mentioning
confidence: 99%
“…Therefore, TRPV3 plays essential roles in epidermal proliferation, differentiation, survival, hair growth, and the development of itch sensation 26 . Several small-molecule inhibitors of TRPV3 have demonstrated analgesic properties in inflammatory and neuropathic pain models 27,28 .…”
Section: Introductionmentioning
confidence: 99%